A benchmark study of automated intra-retinal cyst segmentation algorithms using optical coherence tomography B-scans. (January 2018) - Girish, GN; Anima, VA; Kothari, Abhishek R; Sudeep, PV; Roychowdhury, Sohini; Rajan, Jeny
Highlights: The different automated OCT intra-retinal cyst segmentation methods are reviewed and comparatively analysed for quantitative and qualitative benchmarking purposes. A modular approach to standardize the existing cyst segmentation methods is presented for methodological benchmarking purposes. The methods are analysed for their scalability across image acquisition systems using publicly available cyst segmentation challenge dataset. Factors on the automated cyst segmentation are identified and future directions to improve automated detection and diagnosis of retinal pathologies are discussed. Abstract: (Background and objectives): Retinal cysts are formed by accumulation of fluid in the retina caused by leakages from inflammation or vitreous fractures. Analysis of the retinal cystic spaces holds significance in detection and treatment of several ocular diseases like age-related macular degeneration, diabetic macular edema etc. Thus, segmentation of intra-retinal cysts and quantification of cystic spaces are vital for retinal pathology and severity detection. In the recent years, automated segmentation of intra-retinal cysts using optical coherence tomography B-scans has gained significant importance in the field of retinal image analysis. The objective of this paper is to compare different intra-retinal cyst segmentation algorithms for comparative analysis and benchmarking purposes. (Methods): In this work, we employ a modular approach for standardizing the different segmentation algorithms. Further, we analyze the variations in automated cyst segmentation performances and method scalability across image acquisition systems by using the publicly available cyst segmentation challenge dataset (OPTIMA cyst segmentation challenge). (Results): Several key automated methods are comparatively analyzed using quantitative and qualitative experiments. Our analysis demonstrates the significance of variations in signal-to-noise ratio (SNR), retinal layer morphology and post-processing steps on the automated cyst segmentation processes. (Conclusion): This benchmarking study provides insights towards the scalability of automated processes across vendor-specific imaging modalities to provide guidance for retinal pathology diagnostics and treatment processes.